2003
DOI: 10.1023/a:1026001216033
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We determined the prevalence of GSTP1-Ile105 and GSTP1-Val105 alleles in patients with bronchial asthma and atopic dermatitis and healthy children of 2 groups (randomized and nonatopic control). The GSTP1-Ile105/Val105 genotype determines the resistance to atopic dermatitis (odds ratio=0.51; 95% confidence interval: 0.28-0.92; p=0.023). However, both homozygotes are at high risk of developing atopic dermatitis (near-significant differences).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In detail, four studies were published in the 1990s, nine in the 2000s, and 21 in the last decade. Different geographical areas (and ethnicities) were not uniformly represented: 16 studies [17,18,23,24,27,[32][33][34][35][36][37][38]40,42,45,46] were performed in Eastern Asia (8 in Japan, 6 in Korea, 2 in Taiwan), nine [21,28,31,39,41,43,44,47,48] in Europe (3 in Russia, 2 in Germany, 1 in Finland, Italy, Norway, Switzerland), four [20,22,29,30] in Middle Eastern countries (3 in Turkey, 1 in Israel), two [25,26] in Southern Asia (Bangladesh, India), and one [49] in the United States of America. Another study [19] included patients from multiple Canadian and European centers.…”
Section: Resultsmentioning
confidence: 99%
“…In detail, four studies were published in the 1990s, nine in the 2000s, and 21 in the last decade. Different geographical areas (and ethnicities) were not uniformly represented: 16 studies [17,18,23,24,27,[32][33][34][35][36][37][38]40,42,45,46] were performed in Eastern Asia (8 in Japan, 6 in Korea, 2 in Taiwan), nine [21,28,31,39,41,43,44,47,48] in Europe (3 in Russia, 2 in Germany, 1 in Finland, Italy, Norway, Switzerland), four [20,22,29,30] in Middle Eastern countries (3 in Turkey, 1 in Israel), two [25,26] in Southern Asia (Bangladesh, India), and one [49] in the United States of America. Another study [19] included patients from multiple Canadian and European centers.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows deviation from HWE for GSTP1 gene in four studies of relatively small size (less than 500), including three case–control studies of rather poor quality, 38 , 40 , 41 and a cohort study 42 . Only two of them 41 , 42 performed quality control of genotyping and found no genotyping error, and none of them reported blinded genotyping.…”
Section: Resultsmentioning
confidence: 99%
“…Two SNPs were located in the coding exons: rs1695 (SNP16 in this study) was located in exon 5 and rs4891 (SNP19 in this study) was located in exon 7 (table 2). Ile105Val (SNP16) was a non-synonymous substitution that has been investigated in many previous papers [11,12,13,14,15,16,17]. In addition, we sequenced the promoter region up to 3 kb upstream of exon 1, and identified 8 SNPs, 2 of which were new SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…In 2000, Fryer et al [11] first reported the positive association of a single-nucleotide polymorphism [SNP; 342A→G (Ile105Val); rs1695] of GSTP1 with bronchial hyperresponsiveness, skin pick test and asthma. Subsequently, a positive association of this SNP with asthma was reported in Turkish [12, 13] and Taiwanese [14, 15] populations, and a negative association was reported in Icelandic [16] and Russian [17] populations. An association of this SNP with disease susceptibility and gene environmental interaction were also reported in childhood [15, 18] and occupational asthma [19, 20].…”
Section: Introductionmentioning
confidence: 99%